Concrete resistant to dry-wet cycle corrosion of chloride salts and its recycling method

By preparing natural granite concrete that has undergone the wet and dry cycle of chloride into regenerated coarse aggregate, and preparing optimized formula regenerated coarse aggregate concrete, the problem of concrete being susceptible to chloride ion erosion in the wet and dry cycle environment is solved, significantly improving the mechanical properties and anti-chlorine ion erosion properties of concrete, and achieving efficient reuse of waste materials.

CN117125933BActive Publication Date: 2025-03-14CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310848655.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-03-14
Estimated Expiration
2043-07-12

AI Technical Summary

Technical Problem

In a dry and wet cycle environment, concrete structures are susceptible to chloride ions, resulting in durability problems, and the performance of waste concrete aggregates is poor, resource utilization is low, and environmental pollution is caused.

Method used

By preparing natural granite concrete that has undergone the wet-cycle cycle of chloride into regenerated coarse aggregate, and using it as raw material to prepare regenerated coarse aggregate concrete, the formulation and process flow are optimized to improve the erosion resistance of concrete against wet-cycle cycle of chloride.

Benefits of technology

It significantly improves the compressive strength, split tensile strength, flexural strength and chloride ion corrosion resistance of concrete, meets the specification requirements, extends the service life of concrete, and effectively utilizes waste materials, reducing dependence on natural resources and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004333211950000041
    Figure BDA0004333211950000041
  • Figure BDA0004333211950000042
    Figure BDA0004333211950000042
  • Figure BDA0004333211950000043
    Figure BDA0004333211950000043
Patent Text Reader

Abstract

The invention discloses concrete resistant to dry-wet erosion of chloride salts and a recycling method thereof. A concrete formula capable of resisting erosion of chloride salts is designed, comprising: natural granite coarse aggregate, river sand, cement, fly ash, silica fume, a water reducing agent and water. The prepared concrete can be used as a recycled aggregate for preparing concrete again after being eroded by chloride salts. The mechanical properties of the prepared recycled concrete are better than those of the original concrete, and the chloride ion erosion resistance effect also meets the requirements of the specification. The waste material resources are fully utilized, the dependence on natural resources is reduced, the environmental impact is reduced, and the concrete has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete preparation, and in particular relates to concrete resistant to chlorine salt dry-wet cycle erosion and a recycling method thereof. Background Art

[0002] my country has vast sea areas and a long coastline. A large number of buildings and structures in coastal and northern regions are in a dry-wet cycle environment, and the environment is rich in corrosive media - chloride ions. Chloride ions penetrate into the structure, destroying the steel passivation film and causing steel corrosion. At the same time, in a dry-wet cycle environment, the concrete structure will undergo irreversible deformation, causing cracks in the structure to continue to develop, making it easier for chloride ions to penetrate into the concrete, causing durability problems such as cracking and damage of the concrete structure and corrosion of the steel bars, causing the concrete structure to enter the overhaul stage prematurely or end its service early.

[0003] The performance of discarded concrete aggregates after their service in a dry-wet cycle environment is poor, and most of them are transported to the suburbs for storage and landfill or used as road fill. The utilization level is low, resulting in a waste of resources and possible secondary pollution to the environment. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a method for recycling concrete that is resistant to dry-wet cycle corrosion of chloride salts.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:

[0008] The natural granite concrete which has been subjected to the dry-wet cycle of chloride salt is prepared into recycled coarse aggregate, and then used as raw material to prepare recycled coarse aggregate concrete;

[0009] The recycled coarse aggregate concrete comprises, by mass, 922-987 parts of recycled coarse aggregate, 638-658 parts of river sand, 314-328 parts of Portland cement, 61-67 parts of fly ash, 41-45 parts of silica fume, 1.74-2.15 parts of water reducer and 163-171 parts of water.

[0010] As a preferred embodiment of the method for recycling concrete resistant to chloride-salt dry-wet cycle erosion according to the present invention, the natural granite concrete comprises, by mass, 1072 to 1092 parts of coarse aggregate, 638 to 658 parts of river sand, 314 to 328 parts of Portland cement, 61 to 67 parts of fly ash, 41 to 45 parts of silica fume, 1.74 to 2.15 parts of water reducer, and 163 to 171 parts of water.

[0011] As a preferred scheme of the method for recycling the concrete resistant to dry-wet cycle erosion of chloride salts of the present invention, the ratio of silicate cement, fly ash and silica fume in the natural granite concrete is 15:3:2.

[0012] As a preferred embodiment of the method for recycling the concrete resistant to dry-wet cycle erosion of chloride salts of the present invention, the ratio of the weight of the water to the total weight of the cement, fly ash and silica fume in the natural granite concrete is 0.35 to 0.39.

[0013] As a preferred embodiment of the method for recycling the concrete resistant to dry-wet cycle corrosion of chloride salts of the present invention, the method for preparing the recycled coarse aggregate comprises:

[0014] The natural granite concrete that has been through the chloride salt dry-wet cycle is crushed in the primary stage by a jaw crusher, and then subjected to a heating-cooling cycle treatment to obtain primary crushed coarse aggregate;

[0015] The primary crushed coarse aggregate is crushed in the secondary stage by a rolling crusher, and the obtained coarse aggregate is soaked, cleaned, dried and cooled to obtain recycled coarse aggregate.

[0016] As a preferred scheme of the method for recycling concrete resistant to chloride salt dry-wet cycle erosion according to the present invention, the primary crushing comprises the following steps: the movable jaw of the jaw crusher is set to work at a frequency of 85 to 120 times / min, the feed particle size is less than 125 mm, and the discharge particle size is 10 to 40 mm.

[0017] As a preferred scheme of the method for recycling concrete resistant to dry-wet cycle erosion of chloride salts according to the present invention, the secondary crushing comprises the following steps: the rotor rotation frequency of the rolling crusher is set to 230 to 260 times / min, the rotor deflection angle is 2 to 3°, the movable jaw working frequency is 85 to 125 times / min, and the discharge particle size is controlled to be 0 to 20 mm.

[0018] As a preferred embodiment of the method for recycling the concrete resistant to dry-wet cyclic corrosion of chloride salts of the present invention, the number of cycles of the heating-cooling cycle treatment is 2 to 3 times, and the heating temperature is 400 to 500°C.

[0019] As a preferred embodiment of the method for recycling the concrete resistant to dry-wet cycle corrosion of chloride salts of the present invention, the method for preparing the recycled coarse aggregate concrete comprises:

[0020] First, put the recycled coarse aggregate and river sand into a mixing container and mix them evenly, then add 45-55% water;

[0021] Then, silicate cement, fly ash and silica fume are added into a mixing container and stirred evenly, and a water reducing agent and the remaining water are added and stirred evenly to obtain a mixture;

[0022] The mixed material is loaded into the mold, compacted in three layers during the pouring process, placed on a vibrating table for compaction for 5 to 10 seconds, and removed from the mold after standing still indoors for 24 hours. It is then moved into a standard curing room with a temperature of 20±2°C and a relative humidity of 95±3% and cured for 28 days to obtain recycled coarse aggregate concrete.

[0023] Another object of the present invention is to overcome the deficiencies in the prior art and provide a recycled coarse aggregate concrete prepared by recycling concrete resistant to dry-wet cycle erosion of chloride salts, wherein the recycled coarse aggregate concrete has improved compressive strength, splitting tensile strength, flexural strength and resistance to chloride ion erosion compared to natural granite concrete.

[0024] Beneficial effects of the present invention:

[0025] The invention provides concrete resistant to dry-wet erosion of chloride salts and a recycling method thereof, designs a concrete formula capable of being used for resisting erosion of chloride salts, and the prepared concrete has excellent anti-chloride ion erosion effect, and the concrete can be used as a recycled aggregate for preparing concrete again after being eroded by chloride salts, the prepared recycled concrete has better mechanical properties than the original concrete, and the anti-chloride ion erosion effect also meets the requirements of the specification, fully utilizes waste material resources, reduces dependence on natural resources, reduces environmental impact, and has broad application prospects. DETAILED DESCRIPTION

[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0027] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0028] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0029] The present invention refers to GB / T50081-2019 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" to measure the compressive strength, splitting tensile strength and flexural strength of concrete;

[0030] Refer to GB / T50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" to measure the mass loss rate, relative dynamic elastic modulus and chloride ion corrosion depth;

[0031] Refer to GB / T25177-2010 "Recycled coarse aggregate for concrete" to measure its apparent density, water absorption, crushing value, firmness and chloride ion content.

[0032] The present invention conducts a chloride salt dry-wet cycle area working condition simulation test on concrete according to the following method:

[0033] 1) The four surfaces of the natural granite concrete specimen except the two 100mm×100mm end surfaces were sealed with epoxy resin, and a 30% ultimate load was applied to the concrete specimen using a four-point bending loading device. The spring length was adjusted so that the tensile stress at the edge of the tensile zone of the specimen was 30% of the ultimate tensile stress of the concrete specimen. The concrete specimen was subjected to a dry-wet cycle test under a load-holding state;

[0034] 2) The wet-dry cycle test is to wet first and then dry. Before the wet test begins, a 5% sodium chloride solution by mass should be prepared in a water bath. The test piece should be immersed in the 5% sodium chloride solution by mass for 23 hours, taken out and wiped dry, and allowed to stand at room temperature for 1 hour. Then, it should be placed in an oven at 60°C and dried for 23 hours. The test piece should be taken out and wiped dry, and allowed to stand at room temperature for 1 hour. During this process, the test pieces should be placed neatly with the molding surface facing upward. The distance between adjacent test pieces should be greater than 30 mm, and the sodium chloride liquid level should exceed the top of the test piece by more than 50 mm. 2 days is one cycle, and a total of 72 cycles are performed.

[0035] The water temperature of the above dry-wet cycle is converted by the Nernst-Einstein equation. The converted test temperature is shown in Table 1 below. The water temperature of the first 12 dry-wet cycles is shown in Table 2 below. The water temperature of the 13th dry-wet cycle is the same as the test temperature corresponding to the first month, and so on.

[0036] The Nernst-Einstein equation is expressed as:

[0037]

[0038] Among them, D CL , D0 is the chloride ion diffusion coefficient at temperature T, T0 (K); q is the activation coefficient, which is related to the water-cement ratio. When the water-cement ratio is 0.4, q=6000K.

[0039] Table 1

[0040]

[0041] Table 2

[0042]

[0043] The raw material related parameters used in the present invention are as follows:

[0044] Natural granite coarse aggregate: apparent density, water absorption and crushing value are 2688kg / m 3 , 0.8% and 5.4%, with a particle size of 0 to 20 mm;

[0045] River sand: medium sand, particle size less than 4.75mm, fineness modulus 2.47;

[0046] Cement: Ordinary Portland cement, strength 42.5;

[0047] Fly ash: dry-discharged grade II fly ash;

[0048] Silica fume: SiO2 content 95.8%;

[0049] Water reducing agent: The water reducing efficiency is 25%, and the polycarboxylic acid high performance water reducing agent purchased from Jiangsu Nigao Technology Co., Ltd., model is JK-PCA (type A).

[0050] Example 1

[0051] This embodiment provides a method for preparing natural granite concrete, specifically:

[0052] 1) Weigh the raw materials according to the formula in Table 3:

[0053] Table 3 Concrete formula of different groups

[0054]

[0055] 2) Preparation of concrete:

[0056] Add coarse aggregate and river sand into the mixer and mix evenly for 30 seconds, then add 83 parts of water and continue mixing evenly for 30 seconds;

[0057] Add silicate cement, fly ash and silica fume into a mixer and stir evenly for 30 seconds, then add a water reducer and the remaining water and stir evenly to obtain a mixture;

[0058] The mixed material was loaded into molds of 100mm×100mm×100mm and 100mm×100mm×400mm and compacted in three layers during the pouring process. The completed mold was then placed on a vibrating table for compaction, left to stand indoors for 24 hours before demoulding. It was then moved into a standard curing room with a temperature of 20±2°C and a relative humidity of 95±3% and cured for 28 days to obtain natural granite concrete.

[0059] The concrete prepared with the above different formulations was subjected to dry-wet cycle experiments, and the relevant mechanical properties were measured. The results are shown in Table 4.

[0060] Table 4 Mechanical properties and chloride ion corrosion depth of concrete in different groups after dry-wet cycle test

[0061]

[0062] As can be seen from Table 4, adjusting the ratio of natural granite coarse aggregate to river sand has a significant effect on the mechanical properties and chloride ion corrosion resistance of the concrete. The A group formula is the best concrete formula, while the G group concrete does not add fly ash and silica fume. Its compressive strength after 72 dry-wet cycles (144d) is only 33.2MPa, the splitting tensile strength is 3.1MPa, and the flexural strength is 3.84MPa, and the mechanical properties are poor; its mass loss rate is 1.9%, the relative dynamic elastic modulus is 84.9%, the chloride ion corrosion depth is 20.6mm, and the durability against chloride salt corrosion is poor.

[0063] Example 2

[0064] This embodiment provides a method for preparing recycled coarse aggregate from natural granite concrete after chloride erosion, specifically:

[0065] The concrete specimens of each group of concrete in Example 1 that have undergone 72 (144 days) dry-wet cycles were crushed using a jaw crusher, the movable jaw operating frequency was 100 times / min, the feed particle size was less than 125 mm, and the discharge particle size was 25 mm;

[0066] The recycled coarse aggregate obtained from the primary crushing treatment is heated to 450°C and then cooled, and the cycle is repeated 2 to 3 times. A rolling crusher is used for secondary crushing. The rotor rotation frequency is 250 times / min, the rotor deflection angle is 3°, and the movable jaw working frequency is 100 times / min. The discharge particle size is controlled to be 10 mm. The recycled coarse aggregate is soaked, cleaned, dried and cooled.

[0067] The physical properties of the prepared recycled coarse aggregate were tested, and the results are shown in Table 5.

[0068] Table 5 Physical properties of recycled coarse aggregates obtained from concrete of different groups

[0069]

[0070] As can be seen from Table 5, the physical properties of recycled coarse aggregates prepared from concretes with different formulas after chloride erosion are significantly different. Natural granite contains more hard minerals such as quartz and feldspar, and has a higher resistance to chloride erosion, which slows down the penetration and erosion of chloride ions. At the same time, granite has high hardness and strength, which can ensure the mechanical properties of concrete. The fine particles in river sand help to improve the fluidity and stability of recycled coarse aggregate. Adjusting the density of granite and river sand can make the recycled coarse aggregate have a suitable particle size distribution, which helps to improve the mechanical properties and resistance to chloride ion erosion of concrete.

[0071] Example 3

[0072] This embodiment provides a method for preparing recycled concrete using recycled coarse aggregate prepared from natural granite concrete after chloride corrosion, specifically:

[0073] 1) Take the recycled coarse aggregate obtained in Table 5 as raw material and weigh the raw materials according to the following formula:

[0074] 948 parts of recycled coarse aggregate, 648 parts of river sand, 321 parts of Portland cement, 64 parts of fly ash, 43 parts of silica fume, 2.13 parts of water reducer and 167 parts of water;

[0075] 2) Preparation of recycled concrete:

[0076] Add recycled coarse aggregate and river sand into the mixer and stir evenly for 30 seconds, then add 83 parts of water and continue stirring evenly for 30 seconds;

[0077] Add silicate cement, fly ash and silica fume into a mixer and stir evenly for 30 seconds, then add a water reducer and the remaining water and stir evenly to obtain a mixture;

[0078] The mixed material was loaded into molds of 100mm×100mm×100mm and 100mm×100mm×400mm and compacted in three layers during the pouring process. The completed mold was then placed on a vibrating table for compaction, left to stand indoors for 24 hours before demoulding. It was then moved into a standard curing room with a temperature of 20±2°C and a relative humidity of 95±3% and cured for 28 days to obtain natural granite concrete.

[0079] The recycled concrete prepared with the above different formulations was cured for 28 days and the relevant properties were measured. The results are shown in Table 6.

[0080] Table 6 28d properties of recycled concrete made from different recycled coarse aggregates

[0081]

[0082] It can be seen from Table 6 that the recycled coarse aggregate prepared by using concrete with different formulas in the present invention can achieve good technical effects when reused, and the performance of the recycled coarse aggregate is improved to a certain extent compared with the original concrete. This is because a dense chloride protective layer can be formed on the surface of the recycled coarse aggregate after the chloride salt dry-wet cycle treatment, which can prevent chloride salt erosion to a certain extent, and it meets the requirements of environmental action level E and 100-year design service life of concrete structure in GB / T 50476-2019 "Concrete Structure Durability Design Standard" specification; at the same time, the alkali-active substances in the original concrete will be neutralized or transformed after the chloride salt dry-wet cycle treatment, which reduces the possibility of alkali-aggregate reaction and reduces the cracking and expansion of concrete. After the recycled coarse aggregate is crushed and heated, the particle shape is more uniform and the surface is rougher, which increases the binding force of the cement paste and improves the strength and durability of the recycled concrete.

[0083] Example 4

[0084] This example is used to explore the effect of heat treatment temperature of recycled coarse aggregate and recycled concrete prepared from recycled coarse aggregate in the process of preparing recycled coarse aggregate after dry-wet cycle treatment of chloride salt. Specifically, the temperature of preparing recycled coarse aggregate in Group A in Example 2 is adjusted to 300, 400, 450, and 500°C, and the rest of the process formula is the same as Group A in Example 2. The relevant properties of the recycled coarse aggregate and recycled concrete are measured, and the results are shown in Tables 7 and 8.

[0085] Table 7 Physical properties of recycled coarse aggregates obtained at different heating temperatures

[0086]

[0087] Table 8 28d properties of recycled concrete made from recycled coarse aggregates at different heating temperatures

[0088]

[0089] It can be seen from Tables 7 and 8 that the heating temperature is a key factor affecting the performance of chloride-corroded concrete in the process of preparing it into recycled coarse aggregate. After chloride-corroded concrete, chloride ions in the concrete will penetrate into the interior of the concrete and react with the hydration products in the concrete to form chlorides. Heating can destroy the residual chloride crystal structure, thereby reducing the release and penetration of chloride ions. Secondly, heating can improve the particle shape and surface properties of the recycled coarse aggregate, enable it to better combine with the cement paste, fill the pores and defects in the recycled concrete caused by chloride erosion, and improve the density and mechanical properties of the recycled concrete. In this process, too high or too low heating temperature will affect the structure, porosity, water-cement ratio, etc. of the recycled coarse aggregate, thereby affecting the performance of the obtained recycled concrete.

[0090] Example 5

[0091] This example is used to explore the effect of different amounts of recycled coarse aggregate on the properties of the recycled concrete. Specifically, the amount of recycled coarse aggregate in Group A of Example 3 when preparing concrete is adjusted to 987, 948, 939, and 932 parts, and the rest of the process formula is the same as Group A in Example 3. The relevant properties of the recycled concrete are measured, and the results are shown in Table 9.

[0092] Table 9 28d properties of recycled concrete made with different amounts of recycled coarse aggregate

[0093]

[0094] (Note: The compressive strength of granite concrete refers to the compressive strength of granite coarse aggregate concrete with the same number of parts)

[0095] As can be seen from Table 9, the mechanical properties of the recycled concrete prepared by using the recycled coarse aggregate corroded by chloride salt as raw material are significantly improved compared with the original concrete. After the original concrete is treated with chloride salt dry-wet cycle, chloride salt corrosion will occur inside the concrete, causing the hydration products such as calcium aluminate in the original concrete to undergo denitrification reaction, producing dissolved substances such as calcium chloride and aluminum chloride. These dissolved substances will destroy the structure of the hydration products in the concrete, resulting in a decrease in the strength and durability of the concrete. In the preparation process of recycled aggregate, the heating treatment of the recycled coarse aggregate can remove the adsorbed water and crystallized water therein, reduce the moisture content, and reduce the impact on the water-cement ratio of the concrete.

[0096] In addition, the heating process can also cause the substances in the recycled coarse aggregate to undergo thermal decomposition and deterioration, causing changes in their chemical composition, thereby reducing their adverse effects on concrete. When the recycled coarse aggregate is used as a raw material to prepare recycled concrete, the substances in the recycled coarse aggregate react with substances in other raw materials to form new hydration products. These new hydration products can fill the pores in the recycled concrete caused by chloride salt erosion of the original concrete, enhance the density and structural stability of the recycled concrete, and thus improve the mechanical properties of the recycled concrete.

[0097] In this process, when the content of recycled coarse aggregate is low, its main function is to fill the voids in the recycled concrete and increase the density and strength of the recycled concrete. When the recycled coarse aggregate is used together with other raw materials (river sand, silicate cement, fly ash, silica fume, water reducer) to prepare recycled concrete, the substances in the recycled coarse aggregate react with the substances in other raw materials to form new hydration products. The hydration products can fill the pores caused by chloride erosion in the original concrete (recycled coarse aggregate), thereby reducing the permeability of the recycled concrete and the rate of chloride ion penetration, and improving the durability of the recycled concrete.

[0098] However, too high a content of recycled coarse aggregate may lead to a decrease in the mechanical properties of recycled concrete. Some undesirable components in the recycled coarse aggregate (such as salt content and organic matter) may affect the strength and durability of the recycled concrete. In addition, too high a content of recycled coarse aggregate will increase the water-cement ratio of the recycled concrete, thereby reducing the strength of the recycled concrete. Therefore, in the design of the recycled concrete formula, it is necessary to select an appropriate content of recycled coarse aggregate according to the specific situation. In the scheme of the present invention, the recycled concrete prepared with 948 parts of recycled coarse aggregate, 648 parts of river sand, 321 parts of silicate cement, 64 parts of fly ash, 43 parts of silica fume, 2.13 parts of water reducer and 167 parts of water has the best performance.

[0099] In summary, the present invention proposes a method for recycling concrete resistant to chloride salt dry-wet cycle erosion. First, a concrete resistant to chloride salt dry-wet cycle erosion is prepared by formula optimization. The compressive strength of the concrete after 72 dry-wet cycles (144d) is greater than 36.7MPa, the splitting tensile strength is greater than 3.4MPa, the flexural strength is greater than 4.18MPa, and the mechanical properties are good; the mass loss rate after 72 dry-wet cycles (144d) is less than 1.6%, the relative dynamic elastic modulus is greater than 87.9%, and the durability is good; the chloride ion erosion depth after 72 dry-wet cycles (144d) is less than 19mm, and the chloride salt erosion resistance is good.

[0100] Furthermore, the recycled coarse aggregate obtained from the concrete after the above chloride salt dry-wet cycle is used again in the preparation of concrete. The mechanical properties of the recycled concrete are significantly better than those of the original concrete, and the chloride ion rapid migration coefficient is less than 4×10 -12 m 2 / s, meeting the requirements of environmental action level E and 100-year design service life of concrete structures in GB / T 50476-2019 "Concrete Structure Durability Design Standard".

[0101] The present invention regenerates the concrete corroded by chloride salts by post-processing, thereby making full use of waste material resources, reducing dependence on natural resources, and lowering environmental impact, and has broad application prospects.

[0102] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for recycling concrete resistant to chlorine salt dry-wet cycle corrosion, characterized in that: include, The natural granite concrete which has been subjected to the dry-wet cycle of chloride salt is prepared into recycled coarse aggregate, and then used as raw material to prepare recycled coarse aggregate concrete; The natural granite concrete comprises, by weight, 1072-1092 parts of natural granite coarse aggregate, 638-658 parts of river sand, 314-328 parts of Portland cement, 61-67 parts of fly ash, 41-45 parts of silica fume, 1.74-2.15 parts of water reducer, and 163-171 parts of water; The recycled coarse aggregate concrete comprises, by weight, 922-987 parts of recycled coarse aggregate, 638-658 parts of river sand, 314-328 parts of Portland cement, 61-67 parts of fly ash, 41-45 parts of silica fume, 1.74-2.15 parts of water reducer, and 163-171 parts of water. The method for preparing the recycled coarse aggregate comprises: The natural granite concrete that has undergone the chloride salt dry-wet cycle is crushed by a jaw crusher, and then subjected to a heating-cooling cycle treatment to obtain a primary crushed coarse aggregate. The heating-cooling cycle treatment is repeated 2 to 3 times at a heating temperature of 450°C. The primary crushed coarse aggregate is crushed in the secondary stage by a roller crusher, and the obtained coarse aggregate is soaked, cleaned, dried and cooled to obtain recycled coarse aggregate; The recycled coarse aggregate concrete has improved compressive strength, splitting tensile strength, flexural strength and chloride ion corrosion resistance compared to natural granite concrete.

2. The method for recycling concrete resistant to dry-wet cycle corrosion of chloride salts as claimed in claim 1, characterized in that: In the natural granite concrete, the ratio of silicate cement, fly ash and silica fume is 15:3:

2.

3. The method for recycling concrete resistant to dry-wet cycle corrosion of chloride salts as claimed in claim 1, characterized in that: In the natural granite concrete, the ratio of the weight of the water to the total weight of the cement, fly ash and silica fume is 0.35-0.

39.

4. The method for recycling concrete resistant to chloride salt dry-wet cycle corrosion according to claim 1, characterized in that: In the first-stage crushing, the movable jaw of the jaw crusher is set to work at a frequency of 85 to 120 times / min, the feed particle size is less than 125 mm, and the discharge particle size is 10 to 40 mm.

5. The method for recycling concrete resistant to chloride salt dry-wet cycle corrosion as claimed in claim 1, characterized in that: The secondary crushing, wherein the rotor rotation frequency of the rolling crusher is set to 230-260 times / min, the rotor deflection angle is 2-3°, the movable jaw working frequency is 85-125 times / min, and the discharge particle size is controlled to be 10-20 mm.

6. The method for recycling concrete resistant to chloride salt dry-wet cycle corrosion as claimed in claim 1, characterized in that: The preparation method of the recycled coarse aggregate concrete comprises: First, put the recycled coarse aggregate and river sand into a mixing container and mix them evenly, then add 45-55% water; Then, silicate cement, fly ash and silica fume are added into a mixing container and stirred evenly, and a water reducing agent and the remaining water are added and stirred evenly to obtain a mixture; The mixed material is loaded into the mold and compacted in three layers during the pouring process. It is placed on a vibrating table for compaction for 5 to 10 seconds, left to stand indoors for 24 hours, and then demolded. It is then moved into a standard curing room with a temperature of 20±2℃ and a relative humidity of 95±3% and cured for 28 days to obtain recycled coarse aggregate concrete.

Citation Information

Patent Citations

  • Marine engineering concrete with abrasion resistance and chlorine salt corrosion resistance

    CN110776292A

  • Method for rapidly separating recycled coarse aggregate mortar

    CN113461353A